2021
DOI: 10.3390/cells10061404
|View full text |Cite
|
Sign up to set email alerts
|

Know How to Regrow—Axon Regeneration in the Zebrafish Spinal Cord

Abstract: The capacity for long-distance axon regeneration and functional recovery after spinal cord injury is poor in mammals but remarkable in some vertebrates, including fish and salamanders. The cellular and molecular basis of this interspecies difference is beginning to emerge. This includes the identification of target cells that react to the injury and the cues directing their pro-regenerative responses. Among existing models of successful spinal cord regeneration, the zebrafish is arguably the most understood at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 138 publications
0
10
0
Order By: Relevance
“…Strangely, the situation is quite different in fish and salamanders that have the capacity for long-distance axon regeneration and functional recovery after spinal cord injury. For instance, in the zebrafish, a spinal cord injury is followed by an immediate loss of function at the injury site, but in the long run, recovery is observed, associated with a complex response involving multiple cellular pathways and morphological changes (Tsata and Wehner 2021 ). Clearly, this is an extremely complex process, and there is an increasing understanding that mechanics has a role to play in it.…”
Section: Perspectives Challenges and Opportunitiesmentioning
confidence: 99%
“…Strangely, the situation is quite different in fish and salamanders that have the capacity for long-distance axon regeneration and functional recovery after spinal cord injury. For instance, in the zebrafish, a spinal cord injury is followed by an immediate loss of function at the injury site, but in the long run, recovery is observed, associated with a complex response involving multiple cellular pathways and morphological changes (Tsata and Wehner 2021 ). Clearly, this is an extremely complex process, and there is an increasing understanding that mechanics has a role to play in it.…”
Section: Perspectives Challenges and Opportunitiesmentioning
confidence: 99%
“…In the zebrafish central nervous system, it has been shown that acute inflammation is required for the proper induction of regenerative neurogenesis from neural stem cells ( Kyritsis et al, 2012 ; Tsarouchas et al, 2018 ; Silva et al, 2020 ). In particular, the cellular and molecular events during spinal cord regeneration have been dissected in great detail ( Tsata and Wehner, 2021 ). Upon injury, peripheral neutrophils invade the lesion side immediately followed by macrophages, which play a pivotal role in the subsequent functional regeneration, by producing tumor necrosis factor α and controlling interleukin-1 β-mediated inflammation ( Tsarouchas et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…The capacity for axon regeneration and functional recovery after spinal cord injury is very limited in mammals. In contrast, zebrafish are able to robustly regrow severed axonal connections and recover swimming function, both at larval and adult stages ( Tsata and Wehner, 2021 ). Thus, zebrafish offer a valuable animal model for studying spinal cord injury and regeneration.…”
Section: Before You Beginmentioning
confidence: 99%